A review and analysis of names and designations published for species and varieties of Kalanchoe (Crassulaceae subfam. Cotyledonoideae) by Adolf Engler (1844–1930) between 1892 and 1913 - Smith, Gideon F. (Phytotaxa, 2025)
During his career as a botanist, [Heinrich Gustav] Adolf Engler (1844–1930) validly published names for 15 taxa of Kalanchoe (Crassulaceae subfam. Cotyledonoideae), mostly at the rank of species. Additionally, two designations were published in two of his works that date from 1904 and 1906, respectively. The nomenclature and taxonomy of the names and designations that Engler published in Kalanchoe are reviewed and discussed in a historical context. The types of Engler’s Kalanchoe names are recorded and discussed, and corrections are made to some previous typifications. A selection of Engler’s kalanchoes is illustrated.